Regeneration of Pinus and Quercus After Fire in Mediterranean-Type Ecosystems: Natural Mechanisms and Management Practices - Oliveira,Sandra (2009)
Fire is a natural and frequent event in Mediterranean-type ecosystems. Changes in land use have altered fire regimes, disturbing the natural processes of post-fire regeneration of vegetation. The management of fire-prone and fire-affected areas can be achieved by combining natural and artificial processes of vegetation recovery. Pinus and Quercus species occur naturally in these areas and are most affected by fire. The contrasting mechanisms used by these species to overcome the effects of fire, mainly different reproduction strategies, are examined and the results obtained in previous studies reviewed. Pines are usually obligate seeders and rely on the surviving seed bank, usually protected in canopy cones, for their regeneration. Oaks are mainly resprouters and have higher resilience capacity, recovering more rapidly, but with time these differences are attenuated because Pinus grow faster. The natural processes of regeneration can be enhanced by targeted management practices. Prescribed burning, applied to modify fuel quantity and structure and prevent high-severity fires, is widely used in Mediterranean-type ecosystems and its potential effects are discussed. The process of seeding and seedling plantation and the application of techniques to improve seedlings performance are described, however further investigation concerning the potential impacts of their application is required.